Study on erosion of super duplex stainless steel and nickel aluminium bronze under angled slurry jet impingement - Kok, Weiquan (2019)
Electric submersible pumps are becoming increasingly popular in the gas and oil industry because of their ability to extract large volume of fluids from deep underground. During the extraction process, the pump system is subjected to many erosive elements. In the gas and oil industry, erosion has been a critical economic problem and poses as a serious risk to workers if proper precautions are not taken. This report will be on the study on erosion of Nickel Aluminium Bronze (NAB) and Duplex Stainless Steel (DSS) under angled slurry jet impingement. The samples were tested in an erosion setup under three different jet impingement angles (30°, 60° and 90°). The erosion rates of the different samples were calculated as a function of weight loss and contact surface area. Scanning Electron Microscopy (SEM) was used to detect any changes in the morphology of the samples before and after the erosion. Results showed that the erosion rates of both DSS and NAB samples decreases with increasing jet impingement angle. The results from this experiment could provide more information on the erosion rates of DSS and NAB material so that companies in the oil and gas industry can make better decisions during pump selection.